2016
DOI: 10.1002/anie.201603943
|View full text |Cite
|
Sign up to set email alerts
|

Enaminones as Synthons for a Directed C−H Functionalization: RhIII‐Catalyzed Synthesis of Naphthalenes

Abstract: The use of enaminones as effective synthons for a directed C-H functionalization is reported. Proof-of-concept protocols have been developed for the Rh(III) -catalyzed synthesis of naphthalenes, based on the coupling of enaminones with either alkynes or α-diazo-β-ketoesters. Two inherently reactive functionalities (hydroxy and aldehyde groups) are integrated into the newly formed cyclic framework and a broad range of substituents are tolerated, rendering target products readily available for further elaboratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
69
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(72 citation statements)
references
References 77 publications
3
69
0
Order By: Relevance
“…[13] However,t he most populart ransformation model in such known reactionsa re the condensations initiatedb yt he nucleophilic amino group and/ or the nucleophilic a-C(sp 2 )ÀHb ond. Although other transformations,s uch as C(sp 2 )ÀHc oupling reactions [14] and C=C bond-based cycloaddition reactions, [15] are also occasionally disclosed; the overall diversity of transformationm odelsi ne naminones is not yet abundant.R ecently,w eh ave identified that the C=Cd ouble bond in N,N-disubstituted enaminones is able to undergo af ull cleavage to offer C1 buildingb lock in the construction of pyridines. [16] Under the inspiration of this cleavage model of the C=Cd ouble bond, we envisioned that an alternative synthetic methodf or the synthesis of quinolines might also be designed by employing such bond cleavage as ak ey transformation (Scheme 1).…”
mentioning
confidence: 99%
“…[13] However,t he most populart ransformation model in such known reactionsa re the condensations initiatedb yt he nucleophilic amino group and/ or the nucleophilic a-C(sp 2 )ÀHb ond. Although other transformations,s uch as C(sp 2 )ÀHc oupling reactions [14] and C=C bond-based cycloaddition reactions, [15] are also occasionally disclosed; the overall diversity of transformationm odelsi ne naminones is not yet abundant.R ecently,w eh ave identified that the C=Cd ouble bond in N,N-disubstituted enaminones is able to undergo af ull cleavage to offer C1 buildingb lock in the construction of pyridines. [16] Under the inspiration of this cleavage model of the C=Cd ouble bond, we envisioned that an alternative synthetic methodf or the synthesis of quinolines might also be designed by employing such bond cleavage as ak ey transformation (Scheme 1).…”
mentioning
confidence: 99%
“…The group of Zhu used enaminone starting materials for the synthesis of naphthalene derivatives using either α-diazo-β-ketoesters ( Scheme 3F ) or alkynes ( Scheme 4H ) as coupling partners. 92 In case of α-diazo-β-ketoesters as coupling partners the initial step is an alkylation and good FG tolerance on the substrate was observed. Synthetically useful yields between 50–85% were reported and various alkyl residues including cyclopropyl can be in position R 2 .…”
Section: Ketone Dgsmentioning
confidence: 99%
“…The group of Zhu used enaminone starting materials for the synthesis of naphthalene derivatives using either alkynes ( Scheme 4H ) or α-diazo-β-ketoesters ( Scheme 3F ) as coupling partners. 92 In the case of alkynes, only 1,2-diphenylacetylene was used as reaction partner but good FG tolerance on the substrate was observed and synthetically useful yields between 50–85% were reported. According to the proposed mechanism, the initial step is a Rh-catalysed alkenylation.…”
Section: Ketone Dgsmentioning
confidence: 99%
“…Proof-of-concept protocols have been developed for the Rh III-catalyzed synthesis of naphthalenes, based on the coupling of enaminones 1 with either alkynes 153 or a-diazo-b-ketoesters 154. Two inherently reactive functionalities (hydroxy and aldehyde groups) are integrated into the newly formed cyclic framework and a broad range of substituents are tolerated, rendering target products 155, 156 readily available for further elaboration (Scheme 49) 71.…”
mentioning
confidence: 99%